A Cross-Slab found at St John’s Chapel, Canisbay, Caithness - Nicolson, John (Proceedings of the Society of Antiquaries of Scotland, 1922)
A slab lined grave was located inside the doorway in the western gable of the chapel. The slab which formed the end of the grave was part of a cross-slab of yellow sandstone bearing a plain incised cross with hollows at the intersections of the arms and the shaft. The shaft tapered slightly towards the base. The whole design was enclosed within a rectangular panel. The inside lintel of the door of the chapel and two other long, narrow stones formed the cover of the grave.